2002
DOI: 10.1002/ajmg.a.10950
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked recessive chondrodysplasia punctata: Spectrum of arylsulfatase E gene mutations and expanded clinical variability

Abstract: X-linked chondrodysplasia punctata (CDPX1), due to mutations of the arylsulfatase E (ARSE) gene, is a congenital disorder characterized by abnormalities in cartilage and bone development. We performed mutational analysis of the ARSE gene in a series of 16 male patients, and we found mutations in 12 subjects. Clinical variability was observed among the patients, including severe presentations with early lethality in one of them, and symptoms such as cataract and respiratory distress. This indicates that the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 27 publications
4
40
0
2
Order By: Relevance
“…Thus, molecular analysis of ARSE can assist in providing an accurate recurrence risk to the family. Mothers heterozygous for ARSE mutations have not been considered symptomatic, but some have smaller stature than expected [Sheffield et al, 1998;Brunetti-Pierri et al, 2003]. In our patient sample, the difference in heights was not significant between the five mothers who were ARSE heterozygotes and the four whose sons did not have detectable ARSE mutations (Mann-Whitney test, P ¼ 0.17).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, molecular analysis of ARSE can assist in providing an accurate recurrence risk to the family. Mothers heterozygous for ARSE mutations have not been considered symptomatic, but some have smaller stature than expected [Sheffield et al, 1998;Brunetti-Pierri et al, 2003]. In our patient sample, the difference in heights was not significant between the five mothers who were ARSE heterozygotes and the four whose sons did not have detectable ARSE mutations (Mann-Whitney test, P ¼ 0.17).…”
Section: Discussionmentioning
confidence: 63%
“…Ophthalmologic abnormalities: cataracts, optic disc atrophy, small optic nerves. [Franco et al, 1995;Parenti et al, 1997;Sheffield et al, 1998;Dahl et al, 1999, (follow-up on patient reported by Franco); Brunetti-Pierri et al, 2003;Wolpoe et al, 2004 (patient P2 in this manuscript); Garnier et al, 2006]. and the absence of the allele in a population of normal controls.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast, arylsulfatase E is found in the Golgi compartment (7). Mutations in this gene cause chondrodysplasia punctata, a congenital disorder characterized by abnormalities in cartilage and bone development (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…5 In these experiments, all missense alleles had negligible activity. 9,10 Considering the phenotypic resemblance of warfarin embryopathy in early gestation to BCP, Franco et al 5 (1995) demonstrated that ARSE activity is inhibited in the presence of warfarin, an anticoagulant drug that decreases amounts of active vitamin K. These findings suggested that cases of BCP without ARSE mutations could be caused by inhibition of a normal ARSE enzyme in fetal development by reducing levels of vitamin K. Because placental transport of vitamin K is normally reduced, 11 vitamin K deficiency in the mother would be expected to result in greater vitamin K deficiency in the fetus. This hypothesis is attractive given that there have been several reports of BCP in offspring of both sexes in which gestational vitamin K deficiency was suspected, including mothers with severe hyperemesis gravidarum, 12 small-intestinal obstruction, 13 small-bowel syndrome, 14 pancreatitis, 15 or biliary lithiasis.…”
Section: Original Research Article © American College Of Medical Genementioning
confidence: 99%